2013
DOI: 10.1080/10934529.2013.781881
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals in sediments of the Don Hoi Lot area in the Mae Klong estuary, Thailand

Abstract: The status and seasonal variation of heavy metals in surface sediment were investigated at Don Hoi Lot, located in the Mae Klong estuary, Thailand. Results revealed that all the measured heavy metals, except Zn, in the sediments had lower concentrations than in other nearby estuaries. Only Zn may be of concern for potential negative effects on estuarine biota in the study area. With the exception of Fe, all the studied heavy metals showed seasonal variation, but the patterns were diverse. Organic matter and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Thirteen qualitative papers from Thailand were not included in the calculations of ERI and HHRA [ 11 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ]. The exclusions were mainly due to not all the three metals (Cu, Pb, and Zn) being analyzed and reported in these papers.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen qualitative papers from Thailand were not included in the calculations of ERI and HHRA [ 11 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ]. The exclusions were mainly due to not all the three metals (Cu, Pb, and Zn) being analyzed and reported in these papers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these area was located in a site of recognized ecological interest Don Hoi Lot -the Ramsar site [35]. Many studies reported that biota and sediment of the Mae Klong Estuary has been polluted by human activities including trace element heavy metal [36][37][38].…”
Section: Materials and Methods 1) Study Areamentioning
confidence: 99%
“…Sehingga, jika dibandingkan dengan manusia, kerang lebih resisten terhadap cemaran logam berat dan mampu menyimpannya dalam jumlah tinggi. 11,12 Kerang darah merupakan salah satu sumber makanan tinggi protein dan menjadi sumber daya ekonomis yang cukup diminati masyarakat. Tingginya konsumsi kerang dalam masyarakat ditunjukan dengan tingginya volume produksi kerang di Indonesia mencapai rata-rata 94.247,1 ton/tahun dalam dekade terakhir.…”
Section: Pendahuluanunclassified